PENENTUAN KLASIFIKASI KEMATANGAN DAN KUALITAS CABAI MERAH BESAR (Capsicum annuum L.) MENGGUNAKAN APLIKASI COLOR GRAB - Afdhal Luthfi; Arum Mustika Sari; Gadis Ratna Dewi; Yuyun Dwijayanti; Trias Prima Satya; Anjar Ruspita Sari; Satria Bhirawa Anoraga (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The sortation process of chili is a crucial step in deciding the quality and pricing. Domestic chili production must adopt new technology advancements and adequate post-harvest handling procedures to satisfy the community's needs. This article aims to determine the appropriate post-harvest method to reduce damage and loss of weight in chilies, especially in the sorting and grading process. The method used in assisting the sorting and grading process is by utilizing the Color Grab application and smartphones, namely by converting RGB values into YCbCr, where Cb and Cr values are used to determine the maturity level of chilies. Based on the results of the research that has been done, it can be concluded that the maturity level of half-ripe chili based on the YCbCr color level is Cb value 110-118, Cr 135-147, ripe chili Cb value 119-123, Cr 158-166, very mature chili Cb value 124- 127, Cr 152-157. Therefore, the vitamin C content in half-ripe chili is 1.382 mg/g, ripe chili is 1.311 mg/g, and very mature chili is 1.981 mg/g—the more mature the chili, the higher the vitamin C content in the chili.